Reversible Dihydrogen Activation and Catalytic H/D Exchange with Group 10 Heterometallic Complexes. (7th December 2022) - Garçon, Martí; Phanopoulos, Andreas; White, Andrew J. P.; Crimmin, Mark R.
Abstract: Reaction of a hexagonal planar palladium complex featuring a [PdMg3 H3 ] core with H2 is reversible and leads to the formation of a new [PdMg2 H4 ] tetrahydride species alongside an equivalent of a magnesium hydride co‐product [MgH]. While the reversibility of this process prevented isolation of [PdMg2 H4 ], analogous [PtMg2 H4 ] and [PtZn2 H4 ] complexes could be isolated and characterised through independent syntheses. Computational analysis (DFT, AIM, NCIPlot) of the bonding in a series of heterometallic tetrahydride compounds (Ni–Pt; Mg and Zn) suggests that these complexes are best described as square planar with marginal metal‐metal interactions; the strength of which increases slightly as group 10 is descended and increases from Mg to Zn. DFT calculations support a mechanism for H2 activation involving a ligand‐assisted oxidative addition to Pd. These findings were exploited to develop a catalytic protocol for H/D exchange into magnesium hydride and zinc hydride bonds. Abstract : Reaction of a hexagonal planar palladium complex having a [PdMg3 H3 ] core with H2 is reversible and leads to the formation of a new [PdMg2 H4 ] tetrahydride species. DFT calculations support a mechanism for H2 activation involving a ligand‐assisted oxidative addition to Pd. These findings were exploited to develop a catalytic protocol for H/D exchange into magnesium hydride and zinc hydride bonds.